The effects of various processing conditions on the properties of hydroxyapatite / Teh Yee Ching - Teh, Yee Ching (2017)
The sintering behavior of hydroxyapatite (HA) powder produced by wet chemical precipitation method via three different drying methods, i.e. freeze drying (FD-HA), microwave drying (MD-HA) and oven drying (OD-HA) were investigated over the temperature range of 1050°C to 1350°C. The characterization of HA was assessed in terms of powder morphology, powder element analysis, phase stability, bulk density, microstructure, grain size, Vickers hardness and fracture toughness. Based on these results, the HA powder that demonstrated the optimum properties was chosen for further studies to investigate the effects of microwave sintering on the sinterability of the chosen HA. The microwave sintering carried out in temperature ranging from 950°C to 1250°C. The sinterability of microwave sintered HA was compared to that of conventional pressureless sintered HA. Subsequently, the effects of adding zinc oxide (ZnO) ranging from 0.1 wt% to 1.0 wt% on the sinterability of HA when sintered between 1100°C to 1300°C via conventional pressureless sintering were also evaluated. In the present study, the use of microwave drying accelerates the manufacturing of HA powder as only 15 minutes were required to dry the HA powder (MD-HA) while at least 16 hours and 36 hours drying time were required for conventional oven drying (OD-HA) and freeze drying (FD-HA), respectively. It has been revealed that MD-HA possess overall better sinterability and mechanical properties than OD-HA and FD-HA. The optimum sintering temperature for the synthesized MD-HA was 1200°C with the following properties being recorded: relative density of 97.5%, Vickers hardness of 5.04 GPa and fracture toughness of 1.15 MPam1/2. Besides, decomposition of MD-HA phase upon sintering was not observed in the present work but small amount of tricalcium phosphate was observed in OD-HA when sintered at 1350°C. The current study also revealed that microwave sintering played an important role in enhancing the mechanical properties of HA matrix particularly at low sintering temperature. HA with high fracture toughness value of ~1.85 MPam1/2 was produced at 1050°C via microwave sintering. In addition, the addition of 0.5 wt% of ZnO was found to be beneficial in improving the fracture toughness of HA powder. The results indicated that that the resulting 0.5 wt% ZnO-doped HA sintered body exhibited an increased toughness of to 1.37 MPam1/2 and hardness value to 5.63 GPa when compared to the undoped body (1.16 MPam1/2 for fracture toughness and 4.75 GPa for hardness) at 1150°C via conventional sintering. The main advantageous of this research is the economical and rapid production of HA that exhibited enhanced sinterability at low temperatures that is suitable for the production of biomedical devices without compromising the phase stability and biocompatibility nature of the HA.